Immunopathology of Autoimmune Myasthenia Gravis: Implications for Improved Testing Algorithms and Treatment Strategies - Frykman, Hans; Kumar, Pankaj; Oger, Joel (Frontiers in Neurology, 2020)
Myasthenia gravis (MG) is a heterogeneous condition, characterized by autoantibodies (Abs) that target functionally important structures within neuromuscular junctions (NMJ), thus affecting nerve-to-muscle transmission. MG patients are more often now subgrouped based on the profile of serum autoantibodies, which segregate with clinical presentation, immunopathology, and their response to therapies. The serological testing plays an essential role in confirming MG diagnosis and guiding disease management, although a small percentage of MG patients remain negative for antibodies. With the advancements in new highly effective pathophysiologically-specific immunotherapeutic options, it has become increasingly important to identify the specific Abs responsible for the pathogenicity in individual MG patients. There are several new assays and protocols being developed for the improved detection of Abs in MG patients. This review focuses on the divergent immunopathological mechanisms in MG, and discusses their relevance to improved diagnostic and treatment. We propose a comprehensive “reflex testing,” algorithm for the presence of MG autoantibodies, and foresee that in the near future, the convenience and specificity of novel assays will permit the clinicians to consider them into routine systematic testing, thus stimulating laboratories to make these tests available. Moreover, adopting treatment driven testing algorithms will be crucial to identify subgroups of patients potentially benefiting from novel immunotherapies for MG.